Effect of integrated nutrient management on ber (Ziziphus mauritiana Lam) based horti-pasture system under semi-arid condition of Rajasthan - Meena, L.R.; Yadav, R.S. (Indian Journal of Agroforestry, 2020)
A field investigation during 2010 and 2011 in 20 year old ber plantation was carried out to evaluate the productivity of ber based horti-pastoral system under different nutrient management practices at research farm, ICAR-CSWRI, Avikanagar, Rajasthan. Investigation consisted of evaluation of Cenchrus ciliaris and Cenchrus setigerus in main plot and four nutrient management practices viz. control (T0), sheep manure @ 10 t ha-1 in grasses + 12 kg sheep manure in ber plant-1 (TM), 40+40+20 kg NPK ha-1 in grasses and 500 g Urea+750 g SSP+750 g MOP in ber plant-1 (TF) and 5 t sheep manure +20+20+10 kg NPK ha-1 in grasses and 250 g urea +375 g SSP +375 g MOP + 6 kg sheep manure in ber plant-Â Â 1 (TMF). Results revealed that C. setigerus gave significantly highergreen fodder (21.9 t ha-1), dry matter yield (4.60 t ha-1), seed yield (101 kg ha-1), protein content (7.76 %) and protein yield (225 kg ha-1) than to C. ciliaris. Production of ber leaves, fruit and fuel wood was also found significantly higher with C. setigerus. Application of recommended half dose of NPK (20+20+10 kg ha-1) with 5 t sheep manure ha-1 to grasses and 250 g urea + 375 g SSP + 375 g MOP with 6 kg seep manure plant-1 (TMF) resulted significantly higher green fodder (24.9 t ha-1), dry fodder (4.80 t ha-1), grass seed yield (112 kg ha-1), protein content (8.93%) and protein yield (266 kg ha-1) compared to sole application of organic manures (TM) and no application of either source of nutrients (T0). Further, this nutrient management practice also brought highest benefit: cost ratio (2.14). Comparatively higher net economic return (Rs. 33247 ha-1) was obtained from ber with C. setigerus.